PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN PADA BUDGETARY SLACK DENGAN KOMITMEN ORGANISASI DAN ETIKA SEBAGAI VARIABEL MODERASI - Perdana, Kadek Wisnu; Yasa, Gerianta Wirawan (E-Jurnal Akuntansi, 2017)
Public sector budget is a planning instrument, which contains the goals of public organizations. Budget preparation should focus objectives to the welfare of the Community. Entry otomoni area led to changes in the area of financial management into a performance-based budget with the participation in the preparation the budget. However, the performance assessment based whether or not the budget is reached causing agents perform budgetary slack.. This study uses the organization's commitment and ethics as a moderating variable for the purpose of effect weaken of budget participation on budgetary slack. Location this study in SKPD. Sample selection by purposive sampling. Data were taken through a questionnaire and analyzed using multiple linear regression analysis with interaction or moderated regression analysis (MRA). The results positive effect of budget participation on budgetary slack. Organizational commitment and ethics able moderate and weaken the influence of the positive effect on the budget participation budgetary slack.
Keywords: Participation budgeting, budgetary slack, organizational commitment, ethics